Both the High Affinity Thrombin Receptor (GPIb-IX-V) and GPIIb/IIIa Are Implicated in Expression of Thrombin-induced Platelet Procoagulant Activity - Dicker, Ira B.; Pedicord, Donna L.; Seiffert, Dietmar A.; Jamieson, G.A.; Greco, Nicholas J. (Thrombosis and Haemostasis, 2001)
Platelets activated by -thrombin express surface procoagulant activity (PCA) that accelerates the conversion of prothrombin to α-thrombin. Following activation with 10 nM α-thrombin, the PCA of normal platelets was approximately five-fold higher than that of Bernard-Soulier platelets (lacking GPIb). Normal platelet PCA was inhibited ~50 % by activation in the presence of the anti-GPIb MoAbs LJIb10 or TM60. Moreover, normal platelet PCA was completely abrogated in the presence of a combination of both LJIb10 and c7E3, a MoAb directed against αIIbβ3 (GPIIb/IIIa). In contrast, PCA expressed by Bernard Soulier or Glanzmann platelets was not inhibited by either LJIb10 or c7E3 MoAb. The platelet activating peptide SFLLRN at 10 μM, a concentration which fully activates platelet aggregation and Ca2+ mobilization, generated PCA activity one fifth of that generated by α-thrombin at 10 nM but anti-PAR1 antibodies did not affect thrombin-induced PCA expression. These results demonstrate that GPIb mediates, at least in part, the thrombin-induced activation of platelets that leads to PCA, and that αIIbβ3 is also involved in PCA generation, but these results do not support a major role for PAR1 in this activation.
Keywords: Procoagulant; glycoprotein Ib; thrombin